2021
DOI: 10.1016/j.ebiom.2021.103414
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of four lateral flow immunoassays for anti SARS-CoV-2 antibodies: a head-to-head comparative study

Abstract: Background: SARS-CoV-2 antibody tests are used for population surveillance and might have a future role in individual risk assessment. Lateral flow immunoassays (LFIAs) can deliver results rapidly and at scale, but have widely varying accuracy. Methods: In a laboratory setting, we performed head-to-head comparisons of four LFIAs: the Rapid Test Consortium's AbC-19 TM Rapid Test, OrientGene COVID IgG/IgM Rapid Test Cassette, SureScreen COVID-19 Rapid Test Cassette, and Biomerica COVID-19 IgG/IgM Rapid Test. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…In addition, the Elecsys Anti-SARS-CoV-2 S assay preferentially detects high-affinity IgG antibodies that compete with IgM antibodies ( 23 ), contributing to the lower agreement rates with IgM results. In agreement with previous research on the use of lateral flow assays in unvaccinated individuals ( 38 , 39 ), we also report lower evaluator concordance when reading IgM compared with IgG bands. Jones and colleagues found that IgM bands are often weak positives ( 39 ), consistent with our data in vaccinated individuals, potentially resulting in an increased likelihood of a miscall and contributing to the low reader agreement.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the Elecsys Anti-SARS-CoV-2 S assay preferentially detects high-affinity IgG antibodies that compete with IgM antibodies ( 23 ), contributing to the lower agreement rates with IgM results. In agreement with previous research on the use of lateral flow assays in unvaccinated individuals ( 38 , 39 ), we also report lower evaluator concordance when reading IgM compared with IgG bands. Jones and colleagues found that IgM bands are often weak positives ( 39 ), consistent with our data in vaccinated individuals, potentially resulting in an increased likelihood of a miscall and contributing to the low reader agreement.…”
Section: Discussionsupporting
confidence: 92%
“…In recent publications, that assessed the concordance of the results of different high-throughput automated immunoassays (including our used automated immunoassays), ELISA (included in this study) and RIC (not included) assays, a higher concordance than in our result depending on the used assay was recorded [ 28 ] [ 29 ].…”
Section: Discussionmentioning
confidence: 95%
“…Antibody testing in KCL CHECK used an IgG/IgM test kit based on “lateral flow” technology, sent to participants, which was simple to use and has high validity (under lab conditions) [ 31 ]. Antibody tests can give false positives in up to 2 per 100 tests, through cross-reactivity with antibodies unrelated to SARS-CoV-2, [ 12 , 21 ] which can be problematic in large studies with low prevalence. Testing negative after having had COVID-19 is also a concern, since small numbers of people do not produce anti-spike antibodies, [ 32 , 33 ] they are detected more inconsistently in mild and asymptomatic COVID-19, [ 31 , 34 , 35 ] and decline over time [ 36 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are three key limitations of which to be aware. The first regards the antibody test lateral flow cassettes, which are designed for use by a trained person rather than the general public, and are known to be less sensitive and more inconsistent when testing outside the laboratory and on capillary blood [ 21 , 35 ]. Secondly, as we did not exclude people with missing longitudinal survey we had incomplete data about self-reported items after the baseline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation